Information systems for top level football - Blobel, T.; Lames, M. (Proceedings of the 10th International Symposium on Computer Science in Sports (ISCSS), 2016)
In football clubs there are different isolated sources of information. The result is a fundamental need for a central club information system (CIS) for the management. The development of such a system is the purpose of this research. An analysis of the current situation at football clubs has to be done. Based on that, the structure and design for the software solution could be developed. A prototype and a field test will improve the understanding of the needs and habits of the employees at the club. This new information will run into the further development. That iterative process creates a software model that could fulfill the requirements of a central CIS.